A Critical Study of Misbah Musthofa’s Views on Social Life in Tafsir Al-Iklil Fi Ma'ani Al-Tanzil - Nehru Millat Ahmad; Saicul Anam; Camila Fatah Suroyya; Hithna Rohadatul Aisyi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
This study examines the construction of contextual Qur’anic interpretation in Tafsir al-Iklīl fī Ma‘ānī al-Tanzīl by Misbah Musthofa, focusing on the relationship between the Qur’anic text and the socio-religious realities of Indonesian Muslim society. The study is motivated by the dominance of textual exegetical approaches that insufficiently address contemporary social complexity. The aim is to analyze patterns of contextualization in interpreting Qur’anic verses related to family planning, usury-based banking, Qur’anic recitation competitions (MTQ), and the tahlilan tradition. This research employs a qualitative library-based method with a hermeneutic-contextual approach, socio-historical analysis, and Critical Discourse Analysis. Data are examined through textual identification, contextual mapping, and discursive interpretation. The findings reveal that Misbah Musthofa constructs a dialectical relationship between Qur’anic norms and social reality through ethical emphases such as sincerity, moral responsibility, and social critique. The study concludes that Tafsir al-Iklīl represents a contextual exegetical model contributing to the development of Nusantara Qur’anic hermeneutics.